(untitled) (Bangladesh Agronomy Journal, 2021)
The experiment was carried out at the research field of Agronomy and Farming Systems Division, Bangladesh Sugarcrop Research Institute (BSRI), Ishurdi, Pabna during 2012-2013 to determine the most suitable spacing for sugarbeet cultivation in Bangladesh. The experiment was conducted with nine spacing viz. 50 cm × 20 cm, 60 cm × 20 cm, 70 cm × 20 cm, 50 cm × 25 cm, 60 cm × 25 cm, 70 cm × 25 cm, 50 cm × 30 cm, 60 cm × 30 cm and 70 cm × 30 cm in a randomized complete block design with three replications. The effects of spacing on sugarbeet plantation were observed on growth and growth contributing components (germination percentage, number of leaves plant-1, root length, shoot length, root fresh weight, shoot fresh weight, root dry weight, shoot dry weight, crop growth rate) of sugarbeet. The highest germination percentage (95.67%), number of leaves plant-1 (34.33) at 30 DAS, shoot length (54.07 cm) at 120 DAS, root fresh weight (969.47 g plant-1) at 150 DAS, shoot fresh weight (752.47 g plant-1) at 120 DAS and other growth contributing parameters were obtained with the spacing 70 cm × 30 cm. However, the maximum root length (38.97 cm) was obtained with 50 cm × 20 cm spacing. It was concluded that the wider spacing promoted the growth of individual beet, though the optimum spacing for maximum root growth of sugarbeet was 50 cm × 20 cm. Bangladesh Agron. J. 2020, 23(2): 51-58